2015
DOI: 10.1021/acsami.5b03800
|View full text |Cite
|
Sign up to set email alerts
|

2D Hybrid Nanostructure of Reduced Graphene Oxide–CdS Nanosheet for Enhanced Photocatalysis

Abstract: Graphene-based hybrid nanostructures have recently emerged as a new class of functional materials for light-energy conversion and storage. Here, we have synthesized reduced graphene oxide (RGO)-semiconductor composites to improve the efficiency of photocatalysis. Zero-dimensional CdS nanoparticles (0D), one-dimensional CdS nanorods (1D), and two-dimensional CdS nanosheets (2D) are grafted on the RGO sheet (2D) by a surface modification method using 4-aminothiophenol (4-ATP). Structural analysis confirms the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(121 citation statements)
references
References 61 publications
7
114
0
Order By: Relevance
“…In addition, due to the more positive potential of MoS x conduction band, the latter nanostructure may directly accept electrons from the CdS conduction band . As for the catalytic activity, both heteroatom‐doped graphene and MoS 2 components are expected to act as efficient catalytic sites for the photoreduction of 4‐nitrophenol …”
Section: Resultsmentioning
confidence: 99%
“…In addition, due to the more positive potential of MoS x conduction band, the latter nanostructure may directly accept electrons from the CdS conduction band . As for the catalytic activity, both heteroatom‐doped graphene and MoS 2 components are expected to act as efficient catalytic sites for the photoreduction of 4‐nitrophenol …”
Section: Resultsmentioning
confidence: 99%
“…No diffraction peaks for RGO can be observed in the CdS/RGO composites is due to that the main characteristic peak of RGO at about 25.0 • may be overlapped by the (100) peak of hexagonal CdS. 37,38 Scanning electron microscopy and transmission electron microscopy analysis.-The morphology and structure of the synthesized products have been investigated using SEM and TEM techniques. Figure 2a and 2e present overall SEM images of CdS nanoparticle/RGO and CdS nanorod/RGO, respectively, revealing the uniform sprinkle of nanoparticles and nanorods on graphene nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Xiang et al first constructed graphene/TiO 2 with exposed (001) facets (as shown in Figure ) and graphene/g‐C 3 N 4 2D–2D composite photocatalysts, both of which exhibited significantly enhanced photocatalytic H 2 ‐evolution activities due to the efficient charge separation through 2D–2D coupling interfaces. Subsequently, a series of 2D semiconductor nanosheets/nanoplates (e.g., TiO 2 , CdS, Fe 2 O 3 , SnNb 2 O 6 , BiVO 4 , Bi 2 WO 6 , BiOBr, Cu doped SnS 2 , CoS, ZnIn 2 S 4 , In 2 S 3 layered double hydroxide, and AgBr) have been coupled with graphene nanosheets to fabricate various 2D–2D coupling photocatalyst systems for different applications. For example, Bera et al compared the photocatalytic activities of CdS nanoparticle/RGO, CdS nanorod/RGO, CdS nanosheet/RGO composites by changing the size and morphology of semiconductor nanomaterials (0D, 1D, or 2D) .…”
Section: Design Strategies Of Graphene‐based Composite Photocatalystsmentioning
confidence: 99%